2020
DOI: 10.1007/s00259-020-05085-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age and sex correction on the diagnostic performance of dopamine transporter SPECT

Abstract: Purpose The specific binding ratio (SBR) of 123I-FP-CIT (FP-CIT) in the putamen decreases with age by about 5% per decade and most likely is about 10% higher in females. However, the clinical utility of age and sex correction of the SBR is still a matter of debate. This study tested the impact of age and sex correction on the diagnostic performance of the putamen SBR in three independent patient samples. Methods Research sample: 207 healthy controls (HC) and 438 Parkinson’s disease (PD) patients. Clinical sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…Second, we could not match the sex ratio among groups. A recent study conducted age and sex correlation of dopamine transporter imaging, which showed putaminal dopamine availability was about 10% higher in female than male 18 . However, sex effect was weaker than age effect, and sex effect was most prominent at young age 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we could not match the sex ratio among groups. A recent study conducted age and sex correlation of dopamine transporter imaging, which showed putaminal dopamine availability was about 10% higher in female than male 18 . However, sex effect was weaker than age effect, and sex effect was most prominent at young age 18 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted age and sex correlation of dopamine transporter imaging, which showed putaminal dopamine availability was about 10% higher in female than male 18 . However, sex effect was weaker than age effect, and sex effect was most prominent at young age 18 . In this study of subjects, most subjects were aged over 60 years old, and therefore we can suppose sex effect of striatal monoamine availability might be minimized.…”
Section: Discussionmentioning
confidence: 99%
“…Decision algorithm and practical issues have been previously reviewed [ 1 , 3 , 59 , 60 ]. Importantly, recent technical advances improved the reliability of semi-quantitative analysis of striatal binding, thanks to the better atlas-based delineation of the striatum and normative databases for age standardization [ 61 , 62 ].…”
Section: Neurotransmitter Imagingmentioning
confidence: 99%
“…4 These transporters influence the neural signals the striatum receives. [4][5] Disturbances that affect these transporters may cause Parkinson's disease, a condition intimately linked with the dopaminergic system. [6][7][8][9] It is believed that in Parkinson's disease, more than 70% of the dopamine-producing neurons have died.…”
Section: Image In Medicinementioning
confidence: 99%
“…[10][11] Dopamine transporters can be used as a biomarker for evaluating striatal neuronal function. 5,7 When 99mTc is labeled on the tropane analog TRODAT-1, 99mTc-TRODAT-1 is formed. 8 99mTc-labeled Trodat scintigraphy is an exam that the tracer selectively binds to presynaptic dopamine receptors in the substantia nigra of the midbrain.…”
Section: Image In Medicinementioning
confidence: 99%